Potenziare l'abilità di consapevolezza fonologica: uno studio preliminare sull'efficacia di un percorso educativo attraverso l'utilizzo di tecnologie specifiche - Cristiana Lucarelli; Umberto Bivona; Maria Matilde Nera; Michela Goffredo; Ivan Bernabucci; Bruna Grasselli (LED Edizioni Universitarie, 2016)
Reading-writing learning is the result of the interaction between individual cognitive maturation and standard and informal educational experiences solicited by the environment. A relationship between phonologic awareness and reading-writing learning has been hypothesized; thus, it is important studying the development of the meta-phonologic abilities on nursery school children, to facilitate written language learning in the following primary school. The present study aimed at verifying the effectiveness of a phonological awareness abilities enhancing, by means of a structured software («En Plain») which allows training meta-phonological abilities by means of virtual reality. Within a first group of 32 aged 5 children, 20 of them, who showed higher phonological awareness difficulties, have been selected. Half of them (Experimental Group, EG) was submitted to the experimental training by means of «En Plein», while the others (Control Group, CG) were submitted to the standard educational activities. Data analysis revealed that, despite a significant improvement in both groups, only EG children showed higher levels of improvement, likely due to the specific structure of the educational training (explicit work on the meta-phonological abilities), as well as to the technology which improved children's attention, facilitating learning process. Data suggested the usefulness of including a wider sample, to detect meta-phonological abilities learning critical issues at the beginning of schooling process, as well as prescribing specific empowering training of such abilities to reduce difficulties before structure the reading-writing learning process.